2012
DOI: 10.1210/me.2012-1107
|View full text |Cite
|
Sign up to set email alerts
|

Minireview: The Androgen Receptor in Breast Tissues: Growth Inhibitor, Tumor Suppressor, Oncogene?

Abstract: Androgen receptor (AR) signaling exerts an antiestrogenic, growth-inhibitory influence in normal breast tissue, and this role may be sustained in estrogen receptor α (ERα)-positive luminal breast cancers. Conversely, AR signaling may promote growth of a subset of ERα-negative, AR-positive breast cancers with a molecular apocrine phenotype. Understanding the molecular mechanisms whereby androgens can elicit distinct gene expression programs and opposing proliferative responses in these two breast cancer phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
226
1
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(244 citation statements)
references
References 132 publications
9
226
1
8
Order By: Relevance
“…The AR splice variants expressed in advanced prostate cancer are largely hormone independent transcription factors that contribute to the maintenance of AR signalling in an androgendeplete environment and are resistant to conventional antiandrogenic drugs as they lack a ligand binding domain, the docking site for these drugs. While the role of AR in breast cancer is still being defined, and AR is likely to exert tumour suppressive as well as oncogenic effects depending on the molecular subtype [23], several clinical trials employing antiandrogen therapy in the treatment of women with advanced breast cancer are underway (NCT00468715, NCT01597193, NCT00755885). In the current study, we provide evidence for the first time that C-terminal truncated ARVs recently discovered in prostate cancer cells are also expressed in breast cancer cell lines and in multiple human tissues.…”
Section: G C T a C T C T T C A G C A T T A G T C C T G T G A A G G A mentioning
confidence: 99%
See 1 more Smart Citation
“…The AR splice variants expressed in advanced prostate cancer are largely hormone independent transcription factors that contribute to the maintenance of AR signalling in an androgendeplete environment and are resistant to conventional antiandrogenic drugs as they lack a ligand binding domain, the docking site for these drugs. While the role of AR in breast cancer is still being defined, and AR is likely to exert tumour suppressive as well as oncogenic effects depending on the molecular subtype [23], several clinical trials employing antiandrogen therapy in the treatment of women with advanced breast cancer are underway (NCT00468715, NCT01597193, NCT00755885). In the current study, we provide evidence for the first time that C-terminal truncated ARVs recently discovered in prostate cancer cells are also expressed in breast cancer cell lines and in multiple human tissues.…”
Section: G C T a C T C T T C A G C A T T A G T C C T G T G A A G G A mentioning
confidence: 99%
“…In particular, the role of AR in breast carcinogenesis has been the topic of increasing interest over the past decade. While it is clear that AR is expressed in the large majority of breast cancers, controversy exists over its role, which appears to vary depending on the molecular subtype [23]. To date, studies examining the expression of ARVs in human tissues or malignancies other than the prostate have been limited.…”
Section: Introductionmentioning
confidence: 99%
“…14 AR signaling exerts an antiestrogen, anti-proliferative influence under normal physiologic conditions, and this role may be sustained in ER-positive breast cancer cells. [15][16][17] On the contrary, AR signaling may also promote growth of a subset of ER-negative, AR-positive breast cancers with a molecular apocrine phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of breast cancer risk by receptor subtype have shown inconsistent results (1). The importance of the androgen receptor (AR) as a prognostic factor and a possible treatment target in breast cancer is currently debated (2,3). Immunohistochemical (IHC) expression of AR is reported in 70% to 90% of all invasive breast cancers (4,5).…”
Section: Introductionmentioning
confidence: 99%